(untitled) (Research, Society and Development, 2021)
Instrumentation is a fundamental step in endodontic treatment to promote proper cleaning and shaping of the canal. The objective of this study was to compare the cutting capacity of two reciprocal nickel-titanium systems in simulated canal blocks. Sixty acrylic blocks were used, divided into two groups of reciprocal files (WaveOne Gold - WOG and W-File - WF), each with 30 blocks and divided into 3 groups (n=10) representing the first, second and third uses: WOG1, WOG2, WOG3, WF1, WF2, and WF3, respectively. Ink was injected into the simulated channels, which were covered with laminated paper to avoid affecting the instrumentation. For irrigation, 5mL of saline was used at each instrument change. At the end of instrumentation, the blocks were photographed and analyzed in a computer program to compare the results before and after instrumentation. In the statistical analysis, the tests S Shapiro-Wilk, T for independent samples and Mann Whitney were performed. Under the experimental conditions in which this study was conducted, it is concluded that there were no significant differences in apical transport after the third application. However, the instruments of the W-File group had more conservative preparations with a better centralization capacity compared to the instruments of the WaveOne Gold group, which caused preparations with a larger diameter.